La Relazione di Leopoldo Galeotti sulle scuole del Comune (1870) e le ambivalenze del moderatismo toscano - Cingari, Salvatore (Annali Sismondi, 2016)
The essay deals with Leopoldo Galeotti’s 1870 report about Florentine public schools, a report which so far has not been sufficiently studied by historians. It is useful to study the ambivalence of Tuscan post-Union moderates, divided between a discourse on the acculturation of the lower classes and a different anti-democratic practice. The essay also argues that in the second part of nineteenth-century liberalism was inspired by a view that differs from that of contemporary neoliberalism. While the paradigm of liberalism was based on “exchange”, the neo-liberal one builds upon competition.